113k views
4 votes
Write an equation that has the zero's x={−1,−6}

User Chrisblo
by
4.8k points

1 Answer

4 votes

Answer:

Explanation:

If a zero is x = -1, then the factor, going one step backwards, is (x + 1) = 0; if the other zero is x = -6, then the factor is (x + 6) = 0. Now, going backwards one step further, we FOIL those out:

(x + 1)(x + 6) to get x-squared + 6x + 1x + 6 which combines to


x^2+7x+6=y

FOILing those factors together is the opposite of factoring. Factoring gets you the factors, while FOILing puts them back together in the original equation.

User Sameera Liaynage
by
5.0k points